Present status of the theory of the high-Tc cuprates: General Aspects - Anderson, P.W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The Gutzwiller projected mean-field theory, also called plain vanilla or renormalized meanfield theory, is explained and its successes and possible extensions in describing the phenomenology of the cuprate superconductors are discussed. Throughout, we emphasize that while this is a Hartree—Fock based BCS theory, it embodies fundamental differences from conventional perturbative many body theory which may be characterized by calling it a theory of the doped Mott insulator.